Tribological behaviour of copper (II) oxide nanoparticles based lubricant to improve durability of contact surface - Maizatul Asnida, Hassan (2018)
Nowadays, a mineral oil was the most used lubricant in the market, divided into three types of fully synthetic, semi-synthetic and mineral oil. Since most of the existing lubricants have reached their performance limit, one of the significant scientific task is to develop new lubricant formulation that can achieved energy efficiency and reduce the tribological behaviour across various fields. Lubrication is one of the most effective ways to reduce friction, wear and lower the heat addition. Therefore, better performance of lubricant must be developed to prevent the tribological behaviour and nanoparticles additive help to improve it. The new lubricants also must be good quality and environmental friendly. Nanoparticles were selected in this research because in last few years, nanotechnology was gained researchers attention due to their physical and chemical properties that gives positive effect especially related to lubrication industries. New lubricant was developed to challenge the problem that occurred especially in the mechanical system that related to movement parts, industrial components, automotive industries, tools and others that will affected by friction and wear. In this research, nanoparticles help to improve the properties of lubricants and copper (II) oxide (CuO) have been selected due to their influence at higher and lower concentration control by the parameter used. In the current study, an attempt was made to study the limitation of CuO nanoparticles in SAE 30 in different concentration, investigate the coefficient of friction (COF), specific wear rate (WR) and wear mechanism and to optimize the operation parameter to enhancement the tribology characteristics. The research will be experimentally conducted using wear tribo-tester controlled by Arduino software and the tester move in reciprocating sliding motion. The nanolubricants, are the mixing of the base oil with 0.005%wt and 0.01%wt CuO nanoparticles by using ultrasonic water bath and Response Surface Methodology (RSM) method was used to design the experiment with three type of parameters that have been selected. Result showed the lowers friction was 0.06125 and highest friction occurred at 0.4848 where both were using 0.005%wt concentration of CuO nanoparticles. However, it applied with the combination of different parameters. Added CuO nanoparticles in the base oil, it also may be deceased the wear by 0.2482 when 0.005%wt concentration was used. Most of the experiment conducted has giving the significant reduction of the friction and wear when CuO nanoparticles were added. However, CuO nanoparticles provide an effective reduction of friction and wear in different concentration used but, it still have limitation according to the condition of the parameter. The structure, formed, element properties were observed using Field Emission Scanning Electron Microscope (FESEM) and Energy Dispersive X-Ray (EDX) method therefore, the analysis proved that the present of formation of the tribo-layer or protection layer that occurred during the experiment. The used of CuO nanoparticles were improved the friction and wear due to the affects the tribological behaviour of the lubricant. The optimum value for coefficient of friction (COF) is 0.0613μ and 0.6941 for wear rate (WR) with relevant parameter such as speed, load and concentration are 291.33 rev/min, 7.52kg and 0.0086%wt concentration. From the result, it shows that the CuO nanoparticles at 0.005wt% concentration approached with the lubricant (SAE 30).